A convenient Texas wedding - Whitefeather, Sheri (Texas Cattleman's Club: the impostor., 2018)
"Millionaire Rand Gibson's proposal shocks Allison Cartwright. He needs a wife to debunk his playboy image, and her fresh-faced look is perfect for the role. Allison insists sex is off the table. Yet she fears their bodies will betray them. Though the Irish-born writer wants to stay in America, is she desperate enough to marry a man who could break her heart in the bargain?"-- Page [4] of cover.